The influence of Applicants’ Perceptions of Fairness to Job Offer Acceptance in the Private-sector in Vietnam. - Cao, Vũ Hà Trang (2020)
The structure of the study consists of 5 chapters. In the introductory chapter, it is introduced the research context, research facilities, research objectives and research questions, the scope of the study. Chapter 2 introduces literature review. The content of the theoretical basis involves job offers and application perceptions of fairness. Research gaps are also given in chapter 2 of the study. In the next chapter, the content is the analytical framework and the development of research hypotheses. These contents combine theoretical framework and empirical research results in previous studies. The content of Chapter 4 is the method of research and data analysis. In this chapter, along with describing the techniques used to analyze data, the aggregated data is analyzed. The research hypotheses built in the previous chapter are also tested. The output of empirical analysis in chapter 4 is the basis to develop the final chapter content. Chapter 5 includes conclusions as well as discussion of those conclusions and application.